1984
DOI: 10.1128/jb.158.2.425-429.1984
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization of photosynthetic membrane growth initiation sites in Rhodopseudomonas sphaeroides

Abstract: Putative membrane invagination sites at which intracytoplasmic photosynthetic membrane growth is initiated in Rhodopseudomonas sphaeroides can be isolated in an upper pigmented fraction by rate-zone sedimentation. The intracellular localization of membranes present in the isolated fraction was investigated with the impermeant surface-labeling reagent pyridoxal 5'-phosphate, which has been shown to diffuse into the periplasmic space and to label proteins of both the peripheral cytoplasmic membrane and the matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Therefore, ongoing protein synthesis is required to convert these UPB sites of incorporation of radiolabel to a more invaginated ICM structure. These results are in agreement with previous studies (Niederman et al, 1979;Inamine et al, 1984;Reilly and Niederman, 1986) and demonstrate that A. Separation into ICM and UPB membrane fractions by rate-zone ultracentrifugation on a 5-35% w/w sucrose gradient, following cell disruption.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, ongoing protein synthesis is required to convert these UPB sites of incorporation of radiolabel to a more invaginated ICM structure. These results are in agreement with previous studies (Niederman et al, 1979;Inamine et al, 1984;Reilly and Niederman, 1986) and demonstrate that A. Separation into ICM and UPB membrane fractions by rate-zone ultracentrifugation on a 5-35% w/w sucrose gradient, following cell disruption.…”
Section: Resultssupporting
confidence: 93%
“…1A). Pulse-chase radiolabelling with [S 35 ] methionine was carried out in order to align our experiments with earlier studies which demonstrated that the upper and lower membrane bands have a biosynthetic relationship, and originate from immature and mature membranes respectively (Niederman et al, 1979;Inamine et al, 1984;Reilly and Niederman, 1986). Figure 1B shows that a short pulse of radiolabel is incorporated almost instantaneously into the UPB membrane, with a subsequent decline over the 250 min time-course of the chase with unlabelled methionine.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Figure B and E compares the CN‐PAGE analyses of mature intracytoplasmic membranes (ICM) and the sites of initiation of membrane invagination [upper pigmented band (UPB)] that are enriched in proteins involved in pigment and protein biogenesis (Niederman et al ., ; Woronowicz and Niederman, ; Jackson et al ., ). The sample loadings were balanced for protein content, as seen in the Coomassie stained lanes, so there is far less pigment in the corresponding unstained UPB lanes, reflecting their cellular origin as indentations of the non‐photosynthetic cytoplasmic membrane (Inamine et al ., ; Tucker et al ., ). Figure B,E analyse the FLAG‐LhaA and FLAG‐PucC strain, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%